2022
DOI: 10.1111/pce.14483
|View full text |Cite
|
Sign up to set email alerts
|

Limitation of sucrose biosynthesis shapes carbon partitioning during plant cold acclimation

Abstract: Cold acclimation is a multigenic process by which many plant species increase their freezing tolerance. Stabilization of photosynthesis and carbohydrate metabolism plays a crucial role in cold acclimation. To study regulation of primary and secondary metabolism during cold acclimation of Arabidopsis thaliana, metabolic mutants with deficiencies in either starch or flavonoid metabolism were exposed to 4°C. Photosynthesis was determined together with amounts of carbohydrates, anthocyanins, organic acids and enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…In this study we present an in-depth analysis of a condensed dynamic model of the core central carbon metabolism of Arabidopsis thaliana leaves. It is a model that has already been used to identify a role of limitations in sucrose synthesis in carbon partitioning during acclimation (Kitashova et al 2022). Since it has been shown that light intensity is of great importance for the cold acclimation process of plants and there are complex interactions between cold and light signaling (Szalai et al 2018), a dynamic sensitivity analysis was defined, and new experiments were performed to assess its applicability.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we present an in-depth analysis of a condensed dynamic model of the core central carbon metabolism of Arabidopsis thaliana leaves. It is a model that has already been used to identify a role of limitations in sucrose synthesis in carbon partitioning during acclimation (Kitashova et al 2022). Since it has been shown that light intensity is of great importance for the cold acclimation process of plants and there are complex interactions between cold and light signaling (Szalai et al 2018), a dynamic sensitivity analysis was defined, and new experiments were performed to assess its applicability.…”
Section: Discussionmentioning
confidence: 99%
“…Starch and soluble sugars were extracted and determined as described before (Kitashova et al, 2023). In brief, approx.…”
Section: Methodsmentioning
confidence: 99%
“…Enzyme activities of the central carbohydrate metabolism were quantified photometrically as described before with slight modifications (Kitashova et al, 2023). All enzymes were quantified from the same extract, which consisted of 50 mM HEPES-KOH (pH 7.5), 5 mM MgCl 2 , 2 mM EDTA, 1 mM DTT, 1% (v/v) glycerol, 0.1% (v/v) Triton, and protease inhibitor cocktail for plant cell and tissue extracts in DMSO solution (Sigma-Aldrich ® ).…”
Section: Enzyme Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthocyanins generated from the pathway are part of flavonoids synthesized in plants, which include also proanthocyanidins, flavonols, flavones, aurones, and others from different branches of the flavonoid network. In Arabidopsis thaliana [ 1 ], transiently enhanced accumulation of the anthocyanin pigments is regularly seen in seedlings between day three and day six after seed germination under normal physiological conditions, and the phenotype can also be induced under adverse conditions [ 2 ]. The transient pigmentation of leaf and stem, commonly observed in other species [ 3 , 4 , 5 ] as well, is considered beneficial to plants for protection against stressful environments [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%